Teachers’ Strategies and Challenges in Implementing the Independent Curriculum in English Language Teaching: A Qualitative Descriptive Study - Nurian Supriyatin (TEKILA: Journal of Language Teaching and Literature, 2025)
This study explores English teachers’ strategies and challenges in implementing the Independent Curriculum in English language teaching. The Independent Curriculum emphasizes learner autonomy, differentiated instruction, and flexible learning pathways; however, its implementation in English classrooms presents practical challenges for teachers. This study employed a qualitative descriptive design involving English teachers at the secondary school level. Data were collected through semi-structured interviews and classroom observations to capture teachers’ experiences in planning, implementing, and evaluating English instruction under the Independent Curriculum framework. The data were analyzed using thematic analysis. The findings reveal that teachers employed various strategies to support curriculum implementation, including adapting teaching materials to students’ needs, integrating project-based learning, and using digital media to enhance student engagement. Despite these efforts, teachers faced several challenges, such as limited understanding of curriculum guidelines, insufficient training, time constraints, diverse student proficiency levels, and limited teaching resources. These challenges affected teachers’ confidence and consistency in applying the curriculum principles in English classrooms. The study concludes that while English teachers show positive attitudes and adaptability toward the Independent Curriculum, effective implementation requires continuous professional development, clearer instructional guidance, and institutional support. The findings provide practical insights for teachers, school administrators, and policymakers to improve the implementation of the Independent Curriculum in English language teaching contexts.